Slaves of socorro ebook - Flanagan, John (Brotherband Chronicles, 2014)
The fourth installment in the New York Times bestselling Brotherband series, for fans of Lord of the Rings and Game of Thrones   Hal and his fellow Herons have returned home to Skandia after defeating the pirate captain Zavac and reclaiming Skandia's most prized artifact, the Andomal. With their honor restored, the Herons turn to a new mission: tracking down an old rival turned bitter enemy. Tursgud—leader of the Shark Brotherband and Hal's constant opponent—has turned from a bullying youth into a pirate and slave trader. After Tursgud captures twelve Araluen villagers to sell as slaves, the Heron crew sails into action . . . with the help of one of Araluen's finest Rangers!